US Foreign Policy in the Middle East: The Role of Lobbies and Special Interest Groups - Hadjab, Abdelghanie (Journal of Legal Studies and Researches, 2024)
The lobbies supporting Israel play a gigantic role. The current paper deals with the nature of these groups that support Israel, the backgrounds of their influence, and the network of relationships that connect them with influential actors in American foreign policy, with an analysis of the extent of functional interconnection that exists between the political and religious movements that support Israel.